2013
DOI: 10.1371/journal.pone.0068819
|View full text |Cite
|
Sign up to set email alerts
|

Load Index Metrics for an Optimized Management of Web Services: A Systematic Evaluation

Abstract: The lack of precision to predict service performance through load indices may lead to wrong decisions regarding the use of web services, compromising service performance and raising platform cost unnecessarily. This paper presents experimental studies to qualify the behaviour of load indices in the web service context. The experiments consider three services that generate controlled and significant server demands, four levels of workload for each service and six distinct execution scenarios. The evaluation con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
1
0
5
Order By: Relevance
“…We have shown that benchmarking performance of such complex systems such as the AURIN platform allows to tackle a wide variety of micro-benchmarks, that can collectively provide a first order estimate of that system's overall expected performance. By the same token, it is important to continue exploring industry standard indices to better inform the monitoring application of the overall performance of this and other modules of the framework [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that benchmarking performance of such complex systems such as the AURIN platform allows to tackle a wide variety of micro-benchmarks, that can collectively provide a first order estimate of that system's overall expected performance. By the same token, it is important to continue exploring industry standard indices to better inform the monitoring application of the overall performance of this and other modules of the framework [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…A computação em nuvem surgiu a partir da integração de SOA e outros campos da computação como uma nova proposta de fornecer aplicações, plataformas e recursos computacionais como serviço baseado no modelo de pagamento por uso (BUYYA; BROBERG; GOSCINSKI, 2011). Os Web Services são utilizados na prestação desses serviços e possibilitam a reutilização das funcionalidades por entidades externas integrando diferentes recursos computacionais, tais como, computadores, bases de dados e redes, fornecendo uma ligação lógica que pode ser invocada por um cliente (SOUZA et al, 2013).…”
Section: Contextualizaçãounclassified
“…No entanto, as dificuldades estão na falta de métodos precisos de experimentos que exploram os problemas de disponibilidade, confiabilidade e escalabilidade antes de disponibilizar as aplicações para o mundo real (SAROJADEVI, 2012). A possibilidade de desenvolver, aplicar e avaliar novos índices de desempenho em sistemas orientados a serviços que representem efetivamente uma determinada carga de trabalho imposta a aplicação é uma oportunidade de melhorar a qualidade das aplicações (SOUZA et al, 2013). Bai et al (2011) apresentam uma comparação entre o ambiente de nuvem e o ambiente local para testes de carga.…”
Section: Motivação E Objetivosunclassified
See 2 more Smart Citations